Anti‐TNF and thiopurine therapy in pregnant IBD patients does not significantly alter a panel of B‐cell and T‐cell subsets in 1‐year‐old infants. Issue 4 (April 2018) - Kattah, Michael G.; Milush, Jeffrey M.; Burt, Trevor; McCabe, Robert P.; Whang, Michael I.; Ma, Averil; Mahadevan, Uma
Abstract : Objectives: : Infants exposed to combination therapy with anti‐tumor necrosis factor (anti‐TNF) agents and thiopurines may exhibit increased infections at 1 year of age compared to unexposed infants. We hypothesized that this increased risk of infection is due to abnormal development of the newborn immune system. Methods: : We immunophenotyped B‐cell and T‐cell subsets using multiparameter flow cytometry in 1‐year‐old infants whose mothers were exposed to therapeutic agents for IBD. We analyzed samples from infants exposed to infliximab (IFX) or adalimumab (ADA) monotherapy (IFX/ADA, n = 11), certolizumab pegol (CZP) monotherapy (CZP, n = 4), IFX or ADA plus thiopurine combination therapy (IFX/ADA + IM, n = 4), and CZP plus thiopurine combination therapy (CZP + IM, n = 2). Results: Percentages of B cells, CD4+ T helper cells, T regulatory cells (Tregs), and CD8+ cytotoxic T cells, were similar among the groups. Infants exposed to combination therapy (IFX/ADA + IM) exhibited trends toward fewer CD27+ B cells, switched memory B cells, plasmablasts, interferon gamma (IFNγ)‐producing CD4+ and CD8+ T cells, and CCR5+CD4+ T cells, but these did not reach statistical significance. Conclusions: : Multiparameter immunophenotyping of major B‐cell and T‐cell subsets suggests that the adaptive newborn immune system develops largely unaltered after exposure to combination therapy as compared to anti‐TNF monotherapy.